Comparative analysis of four types of mesoscale eddies in the north pacific subtropical countercurrent region – part I spatial characteristics - An, Mengxuan; Liu, Jie; Liu, Jishan; Sun, Wenjin; Yang, Jingsong; Tan, Wei; Liu, Yu; Sian, Kenny T. C. Lim Kam; Ji, Jinlin; Dong, Changming (Frontiers in Marine Science, 2022)
The North Pacific Subtropical Countercurrent (STCC) region has high mesoscale eddy activities due to its complex circulation structure. This study divides these mesoscale eddies into four types: cyclonic cold-core eddy (CCE), anticyclonic warm-core eddy (AWE), cyclonic warm-core eddy (CWE), and anticyclonic cold-core eddy (ACE) according to the rotation direction of the eddy flow field and the sign of average temperature anomaly within the eddy after spatial high-pass filtering. CCE and ACE are called normal eddies, while CWE and ACE are named abnormal eddies. Using eddy-resolving model data (OFES), this work finds that the abnormal eddy phenomenon mainly occurs in the ocean’s upper layer. The eddy number proportion for CCEs, AWEs, CWEs, and ACEs at the sea surface is 35.60, 32.08, 12.95, and 19.37%. The corresponding average radius is 79.14 ± 3.7, 83.34 ± 3.75, 73.74 ± 4.14, and 79.46 ± 3.89 km, respectively. Each type of eddy’s average amplitude is about 3 cm. Regarding the eddy average eccentricity, the four types of eddies have very close eccentricities, with a range of 0.73 0.76. If the types of eddies are not distinguished, the eddies generated north of 21 °N tend to move southward, while eddies generated south of that latitude tend to move northward. The depth of CCEs, AWEs, CWEs, and ACEs with average eddy nonlinearity larger than one is concentrated in the ocean’s upper layer at 109.0, 116.0, 159.0, and 52.0 m, respectively. This study deepens the understanding of the spatial distribution characteristics of mesoscale eddies in the STCC region.